2002
DOI: 10.1051/0004-6361:20011752
|View full text |Cite
|
Sign up to set email alerts
|

BeppoSAX spectral survey of BL Lacs – New spectra and results

Abstract: Abstract. We present BeppoSAX LECS, MECS, and PDS spectra of eleven X-ray selected BL Lacertae objects. Combining these sources with the ones presented elsewhere we have a sample of 21 BL Lacs from the Einstein Medium Sensitivity and Einstein Slew Survey. The sample shows strong correlations of several physical parameters with the peak frequency of the synchrotron branch of the spectral energy distribution. In particular the peak frequency is correlated with the X-ray spectral shape: objects with the peak near… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 30 publications
4
51
0
Order By: Relevance
“…Beckmann et al 2002). This suggests that there may be commonality in the location of the acceleration region even for jets of vastly different scales.…”
Section: A Jet-disk Model For the Non-thermal X-ray/radio Continuummentioning
confidence: 99%
“…Beckmann et al 2002). This suggests that there may be commonality in the location of the acceleration region even for jets of vastly different scales.…”
Section: A Jet-disk Model For the Non-thermal X-ray/radio Continuummentioning
confidence: 99%
“…They confirmed the ROSAT findings, namely, a strong anticorrelation between X and peak for HBLs and no correlation for LBLs, with an initial increase in X going from LBLs to HBLs (see Padovani et al 2001 for details). Figure 8 shows an updated version of the X -peak plot for BL Lac objects from Padovani et al (2001), including the HBLs studied by Beckmann et al (2002). We have also included in this plot our sources, represented by filled circles.…”
Section: No 2 2002mentioning
confidence: 99%
“…The location of the broadband peaks also suggests a different origin for the X-ray emission of the two classes, namely, an extension of the synchrotron emission likely responsible for the lower energy continuum in HBLs, which typically display steep (energy index X $ 1:5) X-ray spectra, and inverse Compton emission in LBLs, which have harder ( X $ 1) spectra Urry et al 1996;Padovani & Giommi 1996). Beppo-SAX observations of BL Lac objects are confirming this picture (Wolter et al 1998;Padovani et al 2001;Beckmann et al 2002).…”
Section: Introductionmentioning
confidence: 96%
“…According to the classification scheme of Padovani & Giommi (1995), 1ES 0414+009 belongs to the class of high-frequency-peaked BL Lac (HBLs), objects with a synchrotron-emission peak located at UV/soft-X-ray frequencies, or equivalently, sources for which the X-ray emission is dominated by synchrotron radiation. There are several archival measurements of the spectral properties of 1ES 0414+009 in X-rays taken using ASCA (Kubo et al 1998), ROSAT (Brinkmann et al 1995), and BeppoSAX (Beckmann et al 2002). Observations with EXOSAT (Giommi et al 1990;Sambruna et al 1994) showed evidence of temporal variability and strong spectral variations, at times having an X-ray photon index of Γ X < 2.…”
Section: Introductionmentioning
confidence: 99%